Preparation and characterization of silsesquioxane-graphene oxide modified soluble polyimide nanocomposites with excellent dispersibility and enhanced tensile properties. (March 2019) - Hsu, Sheng-Yaw; Lin, Sheng-Chi; Wang, Jeng-An; Cheng, Tzu-Yu; Lin, Chih-Wen; Chen, Yi-Hong; Tsai, De-Hao; Ma, Chen-Chi M.
Graphical abstract: Highlights: A successful grafting of silsesquioxanes (SQ) on graphene oxide (GO). Improved dispersibility of GO in soluble polyimide (SPI) by SQ. A significant enhancement in mechanical properties of SPI through hybridization with SQ@GO. Elongation at break increase to 3X in comparison to bare SPI. Abstract: In this study, a facile synthetic approach was demonstrated for the preparation of graphene oxide (GO)-modified soluble polyimide (SPI) nanocomposites with enhanced mechanical properties. Firstly, a two-step method was employed to form SPI via polymerization of cycloaliphatic dianhydride (bicyclo[2, 2, 2]oct-7-ene-2, 3, 5, 6-tetracarboxylic dianhydride) and aromatic diamine (2, 2′-Bis[4-(4-aminophenoxy)phenyl]propane). Amino-substituted silsesquioxane (SQ) was used to conjugate with GO to form SQ-grafted graphene oxide (SQ@GO) and thermally-treated SQ@GO (TSQ@GO). Fourier-transformed infrared spectroscopy, 29 Si nuclear magnetic resonance spectroscopy, scanning electron microscopy, transmission electron microscopy and X-ray photoelectron spectrometry were used complementarily for the study of the chemical structures of the prepared SQ@GO, TSQ@GO and SPI/TSQ@GO nanocomposite film (i.e., TSQ@GO in SPI matrix). Results show successful synthesis of SQ@GO, TSQ@GO and SPI/TSQ@GO nanocomposite film. With support of excellent dispersibility of TSQ@GO in SPI matrix, the tensile properties of SPI improved significantly via hybridization with TSQ@GO: tensile strength enhanced to 1.3X and elongation at break increased to 3 folds. This study demonstrated a prototype method for fabrication of pre-imidized SPI/TSQ@GO nanocomposite, which has shown the promise for moderate-temperature manufacture (below 200 °C) of emerging electronic applications.